Perubahan Perilaku Open Defecation Free (ODF) melalui Program Sanitasi Total Berbasis Masyarakat (STBM) di Desa Babad Kecamatan Kedungadem Kabupaten Bojonegoro - Abdul Muhid; Sumarkan; Rakhmawati; Lukman Fahmi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2018)
This research aimed to change the behavior of Open Defecation Free (ODF) through Total Sanitation Program of Community-Based. Through Community-Based Research (CBR) approach, it was possible that participatory researchers with communities and partners (stakeholders) preparing plans, conducting and evaluating research results. The results showed that the success of the program was determined by the level of Community participation in the planning, implementation, evaluation and until program sustainability. This was shown by the emergence of Community awareness to change the behavior of Open Defecation Free (ODF) and independently able to solve the problem of sanitation based community by building the decent toilet facilities in participatory. Changing in Open Defecation Free (ODF) behavior through Total Sanitation Program of Community-Based was strongly influenced by the availability of sanitation, the support of all parties, and the changing in the community's understanding of ODF. Total Sanitation Program of Community Based-participatory-based was very effective against the effort to change the behavior of defecation carelessly.